Aktywne formy przeciwdziałania bezrobociu w latach 2000-2004 (na przykładzie Częstochowy) - Wieczorek, Milena; Rączaszek, Andrzej (Active Forms of Striving Against Unemployment Between 2000-2004 on the Example of Częstochowa, 2005)
Within the scope of adaption the Polish employment policy to the directives of the European Union some activities have been undertaken aimed at striving against unemployment, which, within the retrospective view, shall lead to the modernization of a job market and to the decrease in the number of unemployed people. However, to a large extent it will depend on how Poland will make use of the experience of the Member Countries, which were in the similar economic situation at the moment of accession to the European Union.The objective of this article is present the active forms of striving against unemployment which have been undertaken in Częstochowa between 2000-2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 419-436